40 days and 40 nights: Clinical characteristics of major trauma and orthopaedic injury comparing the incubation and lockdown phases of COVID-19 infection. (July 2020) - Ajayi, B.; Trompeter, A.; Arnander, M.; Sedgwick, P.; Lui, D. F.
No abstract available